Evaluating 4G network performance at UTeM campus to facilitate 5G implementation in Malaysia - Mohamed Yunus, Mawarni; Mohamad, Mas Haslinda; Azahar, Khairina Nazihah; Khaidir, Yulindon (Semarak Ilmu Publishing, 2024)
As Malaysia transitions to 5G technology, evaluating 4Gcoverage performance is essential for preparing the groundwork for advanced networks. This project focuses on assessing the radio communication link performance of 4G systems at the University Technical Malaysia Malacca (UTeM) campus. The goal is to assist Mobile Broadband (MBB) service providers in developing efficient long-term strategies for Malaysian university campuses and enhancing 4G coverage. The study conducted measurement campaigns and real-time performance analysis using the G-Net Track app, recording key metrics such as minimum RSRP (-115 dBm off-peak, -117 dBm peak), RSRQ (-18 dB for both off-peak and peak periods), and average SNR (11.178 dB off-peak, 11.003 dB peak). Signal quality varied with 25.3% excellent and 4.5% poor in normal weather, and 21.8% excellent and 5.8% poor in rainy conditions. Proximity to the base station showed the best RSRP of -68 dBm at 56m and the worst at -110 dBm around 915m away. The study concludes that mobile network operator (MNO) performance is influenced by traffic load, weather conditions, and distance from the base station. Understanding these dynamics can help MBB service providers enhance coverage, reliability, and overall user experience on university campuses and beyond. Future research considering additional KPIs and environmental factors will further enrich these insights, supporting robust network planning and management.